PENYULUHAN PROTOKOL KESEHATAN COVID-19 DAN PEMBAGIAN MASKER KEPADA MASYARAKAT DI WILAYAH KECAMATAN LANGSA BARO KOTA LANGSA PROPINSI ACEH - Putri Nahrisah,; Putri Riskina,; Chairul Vidya,; Ayu Irmayana Siregar, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The Covid-19 pandemic that has hit the world, including Indonesia since the beginning of 2020, has made most of the economic activities, education and public services adjusted. The public is directed to carry out activities by implementing the Covid-19 health protocol. Coronavirus disease 2019 (COVID-19) is a respiratory infection caused by an emerging coronavirus that was first recognized as appearing in Wuhan, China, in December 2019. Genetic sequencing of this virus indicates that it is a betacoronavirus closely related to the SARS virus. This community service is carried out in Langsa Baro District, Langsa City. The method used in the form of "mobile" counseling is that we visit crowded places such as schools, markets and coffee shops in two villages, Payabujok Tunong and Lengkong Village. The outreach activities and distribution of masks that have been held have received a good response from the community. The establishment of cooperation between educational institutions and local governments in this case is the Health Office, Public Health Centers and is expected to break the chain of transmission of Covid-19 through counseling on preventive behavior and clean and healthy living behavior.